Persepsi Praktisi Penyiaran terhadap Regulasi Penyiaran di Indonesia: Studi Kasus Program Empat Mata dan Bukan Empat Mata Di Trans7 - Irawan, Rahmat Edi (Bina Nusantara University, 2011)
Broadcasting regulation is one interesting thing to be observed in Indonesia?s television industry development. One television program that mostly having violation of the regulation is Empat Mata which continued with Bukan Empat Mata broadcasted by Trans7. This supports the researcher to do research about how the exact perception of broadcasting practitioners towards broadcasting regulation in Indonesia. The result of qualitative research, which collects data through observation and literature study, shows there is lack of knowledge in broadcasting practitioners about Indonesia?s Broadcasting Commission (KPI) and broadcasting regulation in Indonesia. Besides less socialization, multi-interpretation troubles in some regulations are the probable cause of increasing numbers of violation towards broadcasting regulations. As preventing action, it needs to have open dialog between KPI and broadcasting practitioners as bridging communication of their different authorities, which would be useful to increase quality of television show in Indonesia.